Effects of Alcohol Withdrawal on Sleep Macroarchitecture and Microarchitecture in Female and Male Rats - Jones, Marissa R.; Brandner, Adam J.; Vendruscolo, Leandro F.; Vendruscolo, Janaina C. M.; Koob, George F.; Schmeichel, Brooke E. (Frontiers in Neuroscience, 2022)
The prevalence of sleep disruptions is higher among people with alcohol use disorder (AUD), particularly during alcohol withdrawal, compared to non-AUD individuals. Although women generally have a higher risk of developing sleep disorders, few studies have investigated sex differences in sleep disruptions following chronic alcohol exposure. The present study examined sleep macroarchitecture (time spent asleep or awake and sleep onset latency) and microarchitecture (bout rate and duration and sleep spindle characterization) prior to alcohol vapor exposure (baseline), during acute withdrawal, and through protracted abstinence in female and male rats. Females and males showed reduced time in rapid eye movement (REM) sleep during acute withdrawal, which returned to baseline levels during protracted abstinence. REM sleep onset latency was decreased during protracted abstinence in females only. Furthermore, there was a sex difference observed in overall REM sleep bout rate. Although there were no changes in non-REM sleep time, or to non-REM sleep bout rate or duration, there was an increase in non-REM sleep intra-spindle frequency during acute withdrawal in both females and males. Finally, there was increased wakefulness time and bout duration during acute withdrawal in both females and males. The results demonstrate both macroarchitectural and microarchitectural changes in sleep following chronic alcohol exposure, particularly during acute withdrawal, suggesting the need for therapeutic interventions for sleep disturbances during withdrawal in individuals with AUD. Furthermore, sex differences were observed in REM sleep, highlighting the importance of including both sexes in future alcohol-related sleep studies.